The Influence of Technological Progress on the Culture and Lifestyle of the Dukuh Dalem Village Community and Outsiders - Akmal Ramadhan; Iffa Nur Khofifa; Ressa Putri Amelia; Yuliani Sadida (The International Journal of Politics and Sociology Research, 2021)
This study aims to find out how the influence of technological progress on culture and lifestyle in one of the Garut districts, namely Dukuh Dalem Village and beyond how technology works in influencing the behavior of people in the surrounding environment, namely making people more pragmatic, hedonistic, and secular which leads to generation instant, and can find out the negative and positive sides of technology in everyday life, and know how to maintain culture in the midst of increasingly advanced globalization in an effective way to reduce and overcome the negative impacts of technological advances can be done by synergizing the role of family, education , society, and the State, as well as how the role of technology in influencing the hamlets in the hamlet and outside. Interviews were also conducted with question instruments that can be used to measure the efficiency of how people use technology in their daily lives. and how the existence of technology in the hamlet village is also how the hamlet village responds to increasingly sophisticated technology. Then we can find out the positive and negative effects caused by technology that have an impact on the surrounding environment and even eliminate local culture. Today's technological advances cannot be separated from people's lives. Various information that occurs in various parts of the world can now be directly known to us thanks to technological advances (globalization).